Cycling Performance of Nanocrystalline LiMn2O4 Thin Films via Electrophoresis. (20th May 2012) - Parvathy, S.; Ranjusha, R.; Sujith, K.; Subramanian, K. R. V.; Sivakumar, N.; Nair, Shantikumar V.; Balakrishnan, Avinash
Abstract : The present study demonstrates a novel approach by which titanium foils coated with LiMn2 O4 nanocrystals can be processed into a high-surface-area electrode for rechargeable batteries. A detailed study has been performed to elucidate how surface morphology and redox reaction behaviors underlying these electrodes impact the cyclic and capacity behavior. These nanocrystals were synthesized by in situ sintering and exhibited a uniform size of ∼55 nm. A direct deposition technique based on electrophoresis is employed to coat LiMn2 O4 nanocrystals onto titanium substrates. From the analysis of the relevant electrochemical parameters, an intrinsic correlation between the cyclability and particle size has been deduced and explained in accordance with the Li intercalation/deintercalation process. Depending on the particle size incorporated on these electrodes, it is seen that in terms of capacitance fading, for nanoparticles cyclability is better than their micron-sized counterparts. It has been shown that electrodes based on such nanocrystalline thin film system can allow significant room for improvement in the cyclic performance at the electrode/electrolyte interface.